Computer Science Stack Exchange is a question and answer site for students, researchers and practitioners of computer science. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Below is the lambda expression which I am finding difficult to reduce i.e. I am not able to understand how to go about this problem.

$$(\lambda mn.(\lambda\lambda\lambda$$

I am lost with this.

if anyone could lead me in the right direction that would be much appreciated

share|cite|improve this question

migrated from Oct 10 '12 at 7:49

This question came from our site for theoretical computer scientists and researchers in related fields.

Lambda terms are simplified by the β-reduction rule: $$(\lambda x.M)N\,\rightarrow_\beta\,M[x:=N]$$

It means, if you have a subterm that looks like $(\lambda x.M)N$ (called redex) you can replace it by $M[x:=N]$, which is $M$ with $N$ substituted for $x$. The replacement $M[x:=N]$ is often called contractum. (Capital letters likes $M$ and $N$ are used to denote terms.)

In your case, the first reduction would be:

$$(\underbrace{(\lambda mn.(\lambda\lambda}_{\mbox{redex}})(\lambda \rightarrow_\beta \underbrace{(\lambda n.(\lambda sz.(\lambda}_{\mbox{contractum}}(\lambda$$ where we replaced $m$ with $\lambda$. Note that we now have $\lambda sz$ inside $\lambda sz$ which isn't very convenient (yet allowed). It is better to rename bound variables ($\alpha$-conversion) to be distinct, for example to:

$$(\lambda n.(\lambda uv.(\lambda\lambda$$

Some notes:

  • Substitution applies only to free variables. Bound variables stay always intact.
  • Sometimes substitution is not directly possible. For example, you cannot substitute $x:=y$ into $\lambda y.xy$ because $y$ is bound under $\lambda$. You'd get $\lambda y.yy$ which would change the meaning of the term. So first, you have to rename the bound variable first, for example to $\lambda z.xz$ and then you can safely substitute $x:=y$ to get $\lambda z.yz$. The Wikipedia article gives formal definition of substitution and shows when it's necessary to rename bound variables.
  • Lambda associates to the right, so $\lambda$ is $\lambda s.(\lambda$.
  • Application associates to the left, so $xyz$ is $(xy)z$.
share|cite|improve this answer

An alternative way of expressing a lambda abstraction and reduction. Indexes are used instead of lettered terms based on the order of input. Abstractions are surrounded by []'s

m -> 1, n -> 2, s -> 3, z -> 4
(λmn.(λ = [1 3 (2 3 4)]
(λ = [1 2]
[1 3 (2 3 4)][1 2][1 2]  
[[1 2] 2 (1 2 3)][1 2]   ;1 was replaced with [1 2], remaining terms decremented
[[1 2] 1 ([1 2] 1 2)]    ;1 was replaced with [1 2], remaining terms decremented
[1 ([1 2] 1 2)]          ;1 2 was replaced by 1 ([1 2] 1 2)]
[1 (1 2)]                ;1 2 was replaced by 1 2

The notation above is just a more compact and unambiguous way of expressing lambda abstractions. Compound abstractions reduce to a single normal form automatically, alpha reduction is not needed.

Single positive indexes are used for bound terms. Negative indexes are used for kill terms. Negative indexes are placed last in order of decreasing magnitude.

I = λx.x = [1]
K = λxy.x = [1 -2]
KI = λyx.x = [2 -1]
S = λxyz.xz(yz) = [1 3 (2 3)]

Applying S to K:

[1 3 (2 3)][1 -2]
[[1 -2] 2 (1 2)]  ;1 was replaced with [1 -2], remaining terms decremented
[[.2 -1] (1 2)]   ;reducing: 1 replaced by .2*, -2 decremented (in magnitude) 
[2 -2 -1]         ;(1 2) bound terms become kill terms due to -1.
[2 -1] = KI       ;-2 kill term is void due to surviving 2 term

* the . notation signifies the bound term is from the outer abstraction 
  and must be used to prevent decrementing and double replacement of the
  term until the substitution of all terms in the abstraction is complete.

[2 -1][anything] ;applying KI to anything
[1] = I          ;yeilds I, therefor SK[anything] = [1] = I

Applying K to K:

[1 -2][1 -2]
[[1 -2] -1]  ;kill terms are absorbed and also increase the magnitude of bound terms
[2 -3 -1]    ;applying this result to anything yields K.
[2 -3 -1][anything]
[2 -1]
share|cite|improve this answer
Please add a bit of commentary/motivation. – vonbrand Jan 24 '13 at 9:53
Your answer lacks any description and thus looks like some sort of Soduko puzzle. What is your representation? What are the reduction rules? – Dave Clarke Jan 24 '13 at 18:02
Then do it in the answer; you can edit by clickin on, well, "edit". – Raphael Jan 25 '13 at 11:31
Here is a web based version of an interpreter console for this notation. It does not show the reduction steps but does evaluate correctly for everything that I have been able to throw at it. I am interested in getting feedback on it. – dansalmo Mar 21 '13 at 21:22

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.